Realization of Subsidized Housing Financing on Sharia Services - Sunarta, Desy Arumi; Catherine, Sarkissian; Dylan, Moatti; Alon, Frances; Barra, Lie; Niva, Matteson (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The research location is at Bank Sulselbar Parepare Branch which has a sharia service unit including subsidized housing finance services. Especially in financing. This research focuses on the contracts used in its implementation. In addition, it will also focus on financing mechanisms for subsidized housing ownership in sharia services. Similar to conventional banks that make pawning a banking product, Islamic banks also issue similar products. The presence of sharia products is certainly a relief for some people who care about religious law which prohibits the use of usury in every transaction. In this study, we will discuss the contracts and financing mechanisms for subsidized sharia official housing. The results of the study show that the contract used in the subsidized housing financing mechanism at Bank Sulselbar Syariah Services Parepare Branch is murabahah financing, namely buying and selling based on Islamic bank financial institutions and is applied in consumptive financing and real financing.